PENGARUH ISLAMIC CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Bank Umum Syariah di Indonesia Tahun 2020-2022) - Istighfar, Luhur; Savitri, Enni; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study is to examine the Influence of Islamic Corporate Governance consisting of theSharia Supervisory Board, Independent Board of Commissioners, Audit Committee,Managerial Ownership and Intellectual Capital consisting of Value Added Capital Employed(VACE), Value Added Human Coefficient (VAHC), Value Added Structural Coefficient(VASC) on the Company's Financial Performance. In this study, the sample population was30 Islamic Commercial Banks. Sampling using Purposive Sampling. Data analysis used inthis study is using multiple regression analysis techniques with a statistical approachoperated through the SPSS program.Keywords: Islamic Corporate Governance, Sharia Supervisory Board, Independent Board ofCommissioners, Audit Committee, Managerial Ownership, Intellectual Capital, Value AddedCapital Employed (VACE), Value Added Human Coefficient (VAHC), Value Added StructuralCoefficient (VASC), Company Financial Performance.